PELATIHAN DAN PENDAMPINGAN MENUMBUHKAN JIWA KEWIRAUSAHAAN DI KALANGAN IBU RUMAH TANGGA - Khamimah, Wininatin; Syahrenny, Nenny; Tegowati , Tegowati (Jurnal Kreativitas dan Inovasi (Jurnal Kreanova), 2021)
The Objectives of Community Service Activities Training to Grow the Spirit of Entrepreneurship among Housewives is to provide insight into entrepreneurship so that it becomes an alternative to increase family income and mothers can be more productive using their free time. The method used in the form of training to foster entrepreneurial spirit among housewives and mentoring in the form of consultations about the potential of participants in entrepreneurship and the problems faced. The results obtained from this training activity are: a.) Participants know the importance of entrepreneurship for themselves and their families. b.) Participants are able to identify their potential and know the problems commonly faced in entrepreneurship.Community service activities implemented through this training can benefit a wide audience. Furthermore, it suggests the need for continuity of activities and evaluations after these community service activities are carried out. So that housewives can be more empowered and can contribute in improving family welfare